"Kaj si pa ti kot politik naredil za ta uspeh?!" - Udovič, Boštjan (Slavia Centralis, 2025)
The aim of this article is to establish how the members of the National Assembly use professional terminology in the field of diplomacy. At the same time, it wishes to determine the extent to which diplomatic terminology is established in the Slovenian language. The research was conducted using the siParl 2.0 text corpus, applying both quantitative and qualitative research methods. The results show that it is frequently the case that members of the National Assembly in their speeches use professional terms inadequately (or even incorrectly) or in a semi-colloquial manner. There are also many cases in which professional terms from the field of diplomacy are not used precisely or even sound flat. The analysis also confirms that members of the National Assembly often use simpler (political) language to relate more with their constituents, even when talking about complex issues. However, precisely by refraining from using “professional terminology” when speaking about these issues, they often cause not only a deviation from the terminology, but also confusion about what they really want to express and what message they wish to convey. As a result, the article concludes that a clearer distinction should be made in the debates in the National Assembly between popular (and simpler) political language when it comes to some general political-economic issues, and professional (or more complex) language when it comes to specific issues. This holds especially in the case of the professional language of diplomacy, which ipso facto by its very fabric carries a certain message that does not only have a societal impact, but also an ideological one.
Keywords: corpus SIParl 20.0; diplomacy; Državni zbor Republike Slovenije; jezik diplomacije; Jezik in kultura; jezikovna kultura; korpus siParl 2.0; language culture; MPs; National Assembly; parlament; Parlamenti; poslanke in poslanci; professional language; specialised terminology